Evaluation of learning outcomes of humanities curricula in medical students. A meta-review of narrative and systematic reviews - Coronado-Vázquez, Valle; Antón-Rodríguez, Cristina; Gómez-Salgado, Juan; Ramírez-Durán, María del Valle; Álvarez-Montero, Santiago (Frontiers in Medicine, 2023)
Objectives: To assess the expected learning outcomes of medical humanities subjects in medical studies curricula. To connect those expected learning outcomes with the types of knowledge to be acquired in medical education. Methods: Meta-review of systematic and narrative reviews. Cochrane Library, MEDLINE (Pubmed), Embase, CINAHL, and ERIC were searched. In addition, references from all the included studies were revised, and the ISI Web of Science and DARE were searched. Results: A total of 364 articles were identified, of which six were finally included in the review. Learning outcomes describe the acquisition of knowledge and skills to improve the relationship with patients, as well as the incorporation of tools to reduce burnout and promote professionalism. Programmes that focus on teaching humanities promote diagnostic observation skills, the ability to cope with uncertainty in clinical practice, and the development of empathetic behaviours. Conclusions: The results of this review show heterogeneity in the teaching of medical humanities, both in terms of content and at the formal level. Humanities learning outcomes are part of the necessary knowledge for good clinical practice. Consequently, the epistemological approach provides a valid argument for including the humanities in medical curricula.